The Coup within the Coup: An Analysis of Competing Discourses in 1961-1964 - Bianca de Freitas Linhares; Letícia Baron (Brazilian Political Science Review, 2019)
Written by one of Brazil's leading proponents of Ernesto Laclau's theory of discourse, ‘1961-1964: The Brazilian Dictatorship in Two Coups’ presents an innovative conception of the events that led up to a dictatorship that lasted 21 years. A Laclauean perspective permeates the entire work. One can appreciate the discourse of the main actors involved - political groups, unions, social and military movements - through solid documentary analysis in which special attention is paid to antagonistic debates that reveal the construction of opponents. In this polished and incisive book, second place-winner of the Brazilian Association of Political Science's 2018 Victor Nunes Leal Prize, Daniel de Mendonça revisits his doctoral thesis on the interpretation of the discursive battle that took place between political groups in the pre-coup period.